A Review on fresh concrete, thermal conductivity, and permeability properties of concrete containing cockle shell - Nabilla, Mohamad; Khairunisa, Muthusamy; Hanis Nadiah, Ruslan (Sustainable Building Research Center (ERC) Innovative Durable Building and Infrastructure Research Center, 2022)
Concrete has been used in large volumes for so many years. However, the use of concrete contributes to high cement and aggregate consumption, leading to an increase in material production. The consequences of these activities have been investigated, discussed, and proved that one of the causes of worsening global warming is due to the whole action from concrete industries. On other hand, many researchers found many alternative ways to prevent the extinction of non-renewable material by replacing current material in concrete or cement production with by-products. For example, cockle shell is an aquacultural by-product material that has been dumped after the consumers gain their meat. In this review paper, the new properties, workability, setting time, and other concrete properties containing cockle shells as cement and coarse aggregates such as thermal conductivity, permeability, and porosity, have been discussed.